Exploring the Mechanism of Effectiveness of a Psychoeducational Intervention in a Rehabilitation Program (CopenHeartRFA) for Patients Treated With Ablation for Atrial Fibrillation: A Mixed Methods Study. Issue 4 (July 2019) - Risom, Signe Stelling; Lind, Johanne; Dickson, Victoria Vaughan; Berg, Selina Kikkenborg
Abstract : Background: Patients treated for atrial fibrillation with an ablation can experience decreased mental health. Little is known about the effect of a psychoeducation intervention on this patient group. Objectives: The aim of this study was to explore the effect of a psychoeducation intervention on patients' mental health after participating in a cardiac rehabilitation program, with a focus on elaborating on the lack of mental health improvements. Method: Sequential explanatory mixed methods including secondary analysis of qualitative and quantitative data collected in a randomized rehabilitation trial was performed. Perceived health was measured by a questionnaire (n = 95), and qualitative interviews were performed (n = 10). Results: Patients scoring high on perceived health experienced positive effects of the intervention. Patients scoring low appear to have either low physical capacity and severe atrial fibrillation symptoms, bigger life issues, or lack of social support. Conclusion: A more in-depth understanding of the effect of a psychoeducational intervention included in a cardiac rehabilitation program has been achieved.